LED piano staircase / Muhammad Izzat Syakir Mohd Zailani & Mohd Saiful Amirudin Khalid - Mohd Zailani, Muhammad Izzat Syakir; Khalid, Mohd Saiful Amirudin (2015)
For the Ultrasonic Motion Sensor is very important in this project. Basically, the sensor has 4 legs which are trig leg, echo leg, 5v leg and ground leg. All the legs are connected at arduino but different pins. Ultrasonic Motion Sensor is set only to detect the movement of users each step of the stairs which means every step is detected by different ultrasonic motion sensor. The ultrasonic motion sensor's range is set by the program that created by users. If there are people step on the stair, the sensor will detect the movement and it send the information to arduino and the coding is running. After that, the arduino is working to run the process which is give the information to the LED and Piezoelectric Buzzer as both components producing the outputs. For each step of the stairs, one LED will light up and one buzzer will produce the piano key. Each stairs also have different piano key that have been set through the arduino coding. So the musical like piano will play in code what it has been set off. The function of led for the people walk into the night so the led will light up and also the speaker will produce the sound of the piano.